Pengaruh Variasi Latihan Tri Angle dalam Meningkatkan Akurasi Passing Menggunakan Kaki Bagian Dalam pada Permainan Futsal Siswa Ekstrakurikuler - Daniel Parulian Silaban; Ramadan Ginting; Alan Alfiansyah Putra Karo karo; Dewi Maya Sari (Jurnal Tematik, 2026)
The study aims to apply variations of exercises that are easy to understand and do, namely variations of Tri Angle passing exercises. The purpose of this study is to determine how the influence of Tri Angle exercise variations in improving the accuracy of Passing Using the Inside of the Foot in Futsal Games for extracurricular students of SMP HKBP Sei Mati Medan on passing results. This type of research is quantitative research with the population and sample of research, namely 12 students of SMP HKBP Sei Mati Medan futsal extracurricular students, where in this study using experimental methods and research design using "One Group Pre Test-Post Test Design". Data collection in this study uses data collection techniques in the form of tests. The test used is a test of Nurhasan's futsal game passing skills. Data analysis techniques in this study use statistical data analysis techniques. After conducting the research, the results of this study indicate that the variation of Tri Angle passing exercises has an influence on increasing the accuracy of passing using the inside of the foot for futsal extracurricular students of SMP HKBP Sei Mati Medan in 2025. The variation of Tri Angle passing exercises using the inside of the foot for futsal extracurricular students of SMP HKBP Sei Mati Medan shows that this variation of exercises is suitable to be applied to futsal extracurricular students of SMP HKBP Sei Mati Medan.